REVISIONS TO MASLOW'S HIERARCHICAL MODEL OF BASIC PSYCHOLOGICAL NEEDS - T. Taneva (Trakia Journal of Sciences)
Maslow's hierarchical model of human needs has been identified by some researchers as one of the most cognitively contagious ideas in the behavioral sciences. This model is the most recognized, the most widely known, and it is the basis for other major content theories of motivation. Scientific discussions in the 21st century about the merits and limitations of Maslow's theory of basic needs have periodically intensified, since human actions cannot be explained, predicted or managed without an understanding of their motives, the main content of which are human needs. In spite of the controversial attitude towards the theory, it is widely used in management practice because it is coherent, logical, evolutionarily sound and easy to understand. The paper discusses the principle of extreme deficiency as a condition for maintaining the hierarchy of needs, the ideas of architectural extensions of the pyramid, and rethinking the content of some of the major groups of needs in Maslow's model - self-actualization, status, and belonging/love. The enrichment and expansion of Maslow's hierarchy, especially at the highest levels of the needs of self-actualization and self-transcendence, has the potential to increase the predictive power of the model in exploring people's motivation for activity in different contexts.